THE MOTIVATION TO LEARN ARABIC FOR BEGINNER PUPILS AT MAN 4 BANYUWANGI (Implementation of ARCS Model) - Himatul Istiqomah (Taqdir, 2020)
Abstract Arabic has an important role as the official international language. Besides, Arabic has become a sacred language for Muslims. Because most of the Islamic religious rituals involve Arabic. The text of the holy book of Muslims (al-Qur'an) also uses Arabic. However, there are still many Muslim pupils with inadequate Arabic language skills. Through qualitative research with this documentation technique, the researcher aims to measure the motivation to learn Arabic in beginner pupils at MAN 4 Banyuwangi 2020, which is focused on reading al-Qur'an skills. The instrument used was the Cunningsworth perspective ARCS model motivation questionnaire. The results of this study indicate that the beginner pupils at MAN 4 Banyuwangi 2020 who have high category learning motivation in the Arabic language are more than those who have low category learning motivation in the Arabic language. Keywords: Learning Motivation, ARCS Model, Beginner Pupils, and MAN 4 Banyuwangi.